2015
DOI: 10.1590/0102-311x00194214
|View full text |Cite
|
Sign up to set email alerts
|

Características dos eventos adversos na atenção primária à saúde no Brasil

Abstract: Características dos eventos adversos na atenção primária à saúde no Brasil Características de los eventos adversos en la atención primaria de salud en Brasil

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0
58

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(86 citation statements)
references
References 16 publications
(6 reference statements)
1
15
0
58
Order By: Relevance
“…A Spanish study on the prevalence of AE in PHC evidenced that most of them could have been avoided, that communication problems and organizational factors were the root of many AE (1) . A Brazilian study showed that the communication failure between professionals and users is a contributing factor for the occurrence of PHC incidents (8) . Communication between professionals and users should be promoted in an open and clear manner and the doubts shared for the good understanding of all.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A Spanish study on the prevalence of AE in PHC evidenced that most of them could have been avoided, that communication problems and organizational factors were the root of many AE (1) . A Brazilian study showed that the communication failure between professionals and users is a contributing factor for the occurrence of PHC incidents (8) . Communication between professionals and users should be promoted in an open and clear manner and the doubts shared for the good understanding of all.…”
Section: Discussionmentioning
confidence: 99%
“…In Brazil, the theme gained greater visibility in 2013, starting with the implementation of the National Patient Safety Program (Programa Nacional de Segurança do Paciente). However, it should be considered that there is still little investment in Brazilian research in this setting (8) .…”
Section: Introductionmentioning
confidence: 99%
“…With regard to patient safety, adverse events and incidents seem to be more common in hospitals (5) ; however, they can also occur at other levels of health care, as in primary care (6) . In one study that identified incidents in primary care, the authors recorded an incidence rate ratio of 1.11%, in which 82% caused harm to patients (7) .…”
Section: Introductionmentioning
confidence: 99%
“…26 Cabe salientar que na ocorrência de eventos adversos, os mesmos devem ser notificados à Agência Nacional de Vigilância Sanitária (ANVISA) no sistema de notificações (NOTIVISA), que é um sistema informatizado onde profissionais, instituições e indivíduos podem notificar problemas relacionados ao uso de tecnologias, de processos assistenciais, produtos para a saúde, incidentes e eventos adversos. 27 Destaca-se que a percepção diária de situações de risco colabora para o adequado gerenciamento do cuidado com enfoque na prevenção do erro e o estabelecimento da cultura de segurança na instituição. Os eventos adversos devem ser compreendidos em sua totalidade, considerando o que existe além de sua ocorrência, ou seja, sobrecargas de trabalho, a falta de conhecimento dos profissionais, falta de comunicação, precária infraestrutura institucional, dentre outros.…”
Section: Discussionunclassified